ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN AKSARA JAWA BERBASISINFORMATION AND COMMUNICATION TECHNOLOGIES (ICT) - Ayu Dewi Novitasari; Indah Noviani Wahyuningtyas, Mazaya Salsabila, Muhammad Nofan Zulfahmi (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research focuses on analysing the use of ICT-based Javanese alphabet learning media that have been developed and implemented. The method used in this research is literature study. Data sources in this study were obtained from scientific journals relevant to the research topic with a time span of 2019-2024. The data collection technique is through a systematic literature search using relevant keywords, then continued with content analysis of the sources that have been obtained. The data obtained will be analysed descriptively and comparatively. The use of ICT-based Javanese media is mostly used in the form of mobile with a proportion of 80.0%. In contrast, the least used media types were interactive presentations and videos, at 5.0% each. The features used included interactivity at 65.0%, collaboration at 10.0% and multimedia at 25.0%. Overall, this trend reflects the increasing adaptation of mobile technology in education, especially in teaching Javanese Script. This can be a reference for learning media developers to continue to explore and utilise the potential of mobile technology in supporting the teaching and learning process.